Sociologia della radicalizzazione (Stato, Chiese e pluralismo confessionale, 2024)
Sociology of radicalizationABSTRACT: The new century has seen the expansion of the concept of radicalization, with this term being adopted in various contexts with heterogeneous functions. This paper aims to investigate this phenomenon from a sociological perspective. The first focus is on examining the definition of the term “radicalization” in sociology. Acknowledging that radicalization is not exclusively an Islamic phenomenon, it will be seen that it is considered both a political and a religious matter. In attempting to define this concept, it will be observed how it encompasses various elements that may or may not involve the presence of violent action. Having delved into this initial aspect, the article then explores the reasons that can lead to radicalization and thus the path followed by individuals undergoing 'radicalization.' It will therefore examine the categories of individuals who are more likely to adhere to extremist ideologies, considering both French and Italian contexts. Finally, it will consider how these collected data can enable the construction of a strategy for preventing radicalization.SOMMARIO: 1. Introduzione - 2. Definizioni e ambito di indagine - 3. Traiettorie e intersezioni - 4. Ricerca e prevenzione.